Discrepancies between pathologists and clinicians in interpretation of diagnostic uncertainty in surgical pathology reports - Khairat Battah; Arwa Battah; Iyad Farouji; Shifaa’ Al Qa’qa’; Ruba Malkawi; Maram Abdeljalel; Omar Alzu’bi; Abdelrahman Al-ammori; Ayyub Masuod; Mohammad AlKhreisat (Scientific Reports)
Abstract Pathologists frequently express diagnostic uncertainty in pathology reports, but such expressions may be interpreted differently by clinicians, potentially influencing patient management. This study evaluated how clinicians and pathologists interpret commonly used uncertain phrases in pathology reports and explored factors that influence the degree of certainty conveyed. A two-phase cross-sectional survey was conducted in Jordan. In the first phase, pathologists assessed the level of certainty associated with diagnostic phrases and identified key factors guiding their wording choices. In the second phase, clinicians evaluated the same phrases and reported on the usefulness of different communication methods and comment sections in reports. The results revealed significant variability in interpretation between and within both professional groups. Pathologists’ use of uncertain language was primarily influenced by sample cellularity and diagnostic implications. These findings highlight the importance of improving clarity in pathology reporting and fostering direct communication between clinicians and pathologists to enhance shared understanding and ensure appropriate clinical decision-making.